Feeding strategy of Pleuragramma antarctica investigated by using ecological and ecomorphological approaches - CARLIG, ERICA (Università degli Studi di Siena, 2017)
Antarctic silverfish Pleuragramma antarctica is a keystone species of the coastal ecosystems of the Sothern Ocean. This species is the most abundant pelagic fish in the coastal waters of Antarctica, where it plays a pivotal role in the trophic web as the major link between lower and higher trophic levels. Due to the ecological importance of this species, over the last decades many studies on biology and ecology of P. antarctica were carried out. Despite previous studies have provided an overall picture of the trophic ecology of the Antarctic silverfish, important questions remain. Among them, the opportunistic versus selective feeding habit of the species wasn't still investigated, even if this information holds potential to highlight mechanisms and dynamics of the Antarctic silverfish relationship with the other components of its environment. The investigations on the capability of the species at using food resources can give information about its adaptability to ecological changes. Such a piece of information gains further value if contextualized in the frame of the environmental changes ongoing at a rapid pace in polar regions. The aim of my work is to improve present knowledge on the feeding ecology of the Antarctic silverfish highlighting its feeding habits to assess its possible ability to adapt to variations in the availability of prey caused by climate change or overfishing of krill. The research developed within my PhD program contributes to the PNRA (Italian National Program for Research in Antarctica) project RAISE (Integrate Research on Antarctic Silverfish Ecology in the Ross Sea). The study was divided in two parts, the first one was a purely ecological analysis based on the stomach contents of samples collected in different sectors of the Southern Ocean, the second one was an ecomorphological focus on traits involved in feeding activity of the species. In the ecological analysis, I detected evident differences in the diet of the specimens coming from three different zones (Ross Sea, Dumont ...